PEREMPUAN – PEREMPUAN DALAM USAHA GADO-GADO WARA-WIRI KOTA JAMBI 1962 – 2020 - Khotimah, Husnul; Heidi Karmela, Siti; Azmi, Ulul (Universitas Batanghari Jambi, 2025)
The problem in this research concerns women who work at the Gado-Gado Wara-Wiri stall. The main problem in this research is the life, career and role of women in the traditional culinary business Gado-gado Wara-Wiri 1962 – 2020. The aim of this research refers to the problems raised, so the aim is to explain the role and position of women who were figures/actors in a historical event and how to divide the roles into working women and housewives. The method used in this research is a historical research method which consists of several stages, namely heuristics, criticism, interpretation and historiography. The primary source used in this research was interviews with women workers and Gado-Gado Wara-Wiri entrepreneurs in Jambi City. Meanwhile, secondary sources used are books, theses, journals and internet sources. The research results provide an explanation of the activities of women working in the Gado-Gado Wara-Wiri business in the city, for a very long time, especially since 1962, this gado-gado business has been managed by women both from the family and recruiting employees from the surrounding community who need work to meet their needs or help their husbands to earn a living. Apart from that, researchers also found that women can carry out a dual role, where apart from being workers, women are also not free from their responsibilities as housewives.